Association Between Metabolic Syndrome and Risk of Renal Cell Cancer: A Meta-Analysis - Du, Wurong; Guo, Kaibo; Jin, Huimin; Sun, Leitao; Ruan, Shanming; Song, Qiaoling (Frontiers in Oncology, 2022)
Background: Metabolic syndrome (MetS) has been related to increased risks of a variety of cancers. However, the association between MetS and the risk of renal cell cancer (RCC) remains not fully determined. This meta-analysis was conducted to investigate whether MetS is independently associated with the risk of RCC in adults. Methods: Relevant observational studies were obtained by searching PubMed, Embase, Cochrane’s Library, and Web of Science databases. Study characteristics and outcome data were extracted independently by two authors. The random-effect model was used for meta-analysis considering the possible influence of between-study heterogeneity. Predefined subgroup analyses were used to evaluate the possible influences of study characteristics on the outcome. Results: Eight studies involving 10,601,006 participants contributed to the meta-analysis. Results showed that MetS was independently associated with a higher risk of RCC in adult population (risk ratio [RR]: 1.62, 95% confidence interval [CI]: 1.41 to 1.87, p<0.001; I2=85%). Subgroup analyses showed consistent association in men (RR: 1.52, 95% CI: 1.23 to 1.89, p<0.001) and in women (RR: 1.71, 95% CI: 1.28 to 2.27, p<0.001), in Asians (RR: 1.51, 95% CI: 1.25 to 1.83, p<0.001) and in Caucasians (RR: 1.76, 95% CI: 1.46 to 2.12, p<0.001), and in community derived (RR: 1.56, 95% CI: 1.34 to 1.82, p<0.001) and non-community derived population (RR: 1.87, 95% CI: 1.71 to 2.04, p<0.001). Differences in study design or quality score also did not significantly affect the association (p for subgroup difference both >0.05). Conclusions: MetS may be independently associated with RCC in adult population.